It Can Be a “Very Fine Line”: Professional Footballers’ Perceptions of the Conceptual Divide Between Bullying and Banter - Newman, James A.; Warburton, Victoria E.; Russell, Kate (Frontiers in Psychology, 2022)
This study explores professional footballers’ perceptions of where banter crosses the conceptual line into bullying. The study’s focus is of importance, given the impact that abusive behaviors have been found to have on the welfare and safeguarding of English professional footballers. A phenomenological approach was adopted, which focused on the essence of the participants’ perceptions and experiences. Guided by Interpretative Phenomenological Analysis (IPA), individual semi-structured interviews (MDuration = 44.10 min, SD = 10.81) were conducted with 18 male professional footballers (Mage = 19.83 years, SD = 2.96) from three Premier League and Championship football clubs. The findings from this study revealed several key superordinate themes in relation to the dividing line between bullying and banter. These themes included “perception,” “intentionality,” “detecting the line,” and “having a bit of banter.” The findings demonstrate how perceptions of bullying and banter are nuanced by individual differences among the players and the culture of the professional football context. Specifically, it was found that the professional football context can legitimize forms of humor blurring the lines between bullying and banter, challenging the typically positive view of the concept of banter in this environment. From an applied perspective, these findings highlight the need for coaches, players, and football clubs more broadly to address cultural expectations around banter in their environment, while educating individuals around their own perceptions of bullying and banter.